2008
DOI: 10.1128/iai.01738-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Translocon Proteins of Vibrio parahaemolyticus Type III Secretion System 2

Abstract: The type III secretion system (T3SS) translocon complex is composed of several associated proteins, which form a translocation channel through the host cell plasma membrane. These proteins are key molecules that are involved in the pathogenicity of many T3SS-positive bacteria, because they are necessary to deliver effector proteins into host cells. A T3SS designated T3SS2 of Vibrio parahaemolyticus is thought to be related to the enterotoxicity of this bacterium in humans, but the effector translocation mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 42 publications
2
61
0
1
Order By: Relevance
“…(ii) Two strains (VPe23 and VPe28, both tdh negative and trh negative) representing strains containing T3SS2 genes such as vopB2 and vscC2, encoding translocation proteins (10,26), vopT and vopP, encoding effector proteins (9,26), and other genes located on the pathogenicity island (VP-PAI), such as vopC, encoding a gene homologous to the Escherichia coli cytotoxic necrotizing factor, and VPA1376, encoding a protein homologous to Vibrio cholerae VPI protein (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) Two strains (VPe23 and VPe28, both tdh negative and trh negative) representing strains containing T3SS2 genes such as vopB2 and vscC2, encoding translocation proteins (10,26), vopT and vopP, encoding effector proteins (9,26), and other genes located on the pathogenicity island (VP-PAI), such as vopC, encoding a gene homologous to the Escherichia coli cytotoxic necrotizing factor, and VPA1376, encoding a protein homologous to Vibrio cholerae VPI protein (12).…”
Section: Methodsmentioning
confidence: 99%
“…These data, together with other data obtained in recent years (12,19,28), indicated that TDH or TRH is not the only bacterial factor determining V. parahaemolyticus virulence and that other factors might contribute to the pathogenic potential directed to human hosts. A number of these factors have been subsequently detected and well characterized (10,12,20,28). Genome sequencing of the V. parahaemolyticus clinical strain RIMD2210633 revealed that this bacterial species possesses two sets of type 3 secretion system (T3SS) genes: T3SS1, located on chromosome 1, and T3SS2, located on chromosome…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T3SS2 is found only in Kanagawa phenomenon (KP)-positive strains and produces enterotoxicity that can be assayed using the rabbit ileal loop model (29). Recently, Kodama et al identified two T3SS2 translocon proteins (VopB2, VopD2) ; translocon deletion strains lack the ability to cause fluid accumulation (30). Those studies strongly imply T3SS2 involvement in the enterotoxicity of V. parahaemolyticus and, consequently, the production of Vp-induced diarrhea.…”
Section: Thermostable Direct Hemolysin (Tdh) and Tdh-related Hemolysimentioning
confidence: 99%
“…독 (TDH-related hemolysin, TRH), serine protease 및 type III secretion systems (TTSS1과 2)를 통해 분비되는 각종 effector 단백질 등이 보고되어 있으나 정확한 병원성 기작에 관한 설명은 아직도 많이 부족한 실정이다 (Honda and Iida, 1993;Lee et al, 2002;Makino et al, 2003;Park et al, 2004;Kodama et al, 2007;Kodama et al, 2008).…”
unclassified